IMPLEMENTASI UNDANG- UNDANG NOMOR 11 TAHUN 2012 TENTANG SISTEM PERADILAN PIDANA ANAK DALAM UPAYA MELINDUNGI KEPENTINGAN ANAK - Nevey Varida Ariani (Fakultas Hukum Universitas Muhammadiyah Yogyakarta, 2014)
Children are a mandate from God Almighty which in them laid a dignity as human beings. Children need protection against negative effects of a fast-growing developmnet. This essay is trying to discuss about how’s the implementation of the law of SPPA and the Government of Indonesia’s efforts in protecting children especially those who are conflicted with the law in accordance to The Law number 11 Year 2012. The method applied in this essay is qualitative socio-legal approach, based on the library data. In the investigation process, prosecution until the proceedings, there still be diversion process Is ultimately enforced considering the children’s age and the penalties are not over than 7 years. If this diversion process is not applicable then the judicial process is becoming ultimum remedium, putting the children in LPAS, LPAK and LPKS. Those institutions are expected to give new hopes to children who’s dealing with the legal matters. Through the approching system in Juvenile Criminal Court Process from investigators, prosecutors, judges, advocates to the public counselor, both the Ministry of Law and Human Rights and the Social Ministry, it is necessary to establish a clear coordination and role in implementing the Juvenile Criminal Court System.